ROLE OF COOPERATION IN THE IMPROVEMENT OF THE AGRICULTURAL ECONOMY - Sitanggang, Melva (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Indonesia is an agricultural country rich innatural resources and livelihood of theIndonesian population of predominantlyagricultural products. In the development of theagricultural economy caused by a problem in thefield of agriculture as well as in the availabilityof venture capital that will be used by farmers inthe provision of seeds and fertilizer as well asmaintenance until production is required for therole of cooperatives in alleviating bebab offarmers.According to the Act - Act No. 25 in 1992, saidthat "Cooperatives are business entities whosemembers - the person or legal entity whichbases its cooperative activities based on theprinciple of cooperation as well as peopleseconomic movement based on the principle ofthe family" With the role of cooperatives in theprovision of soft loans in the availability ofventure capital and cooperatives can play a rolein the marketing of agricultural products. Inaddition to the effort, this study also describesthe effect of the economy toward ter cooperativefarmers and also to the social and cultural life ofsociety. And the role of cooperatives inincreasing the incomes of farming communitiesand also its role in the sustainability ofagriculture and social life.KEY WORDS : agriculture, farmers